Mitigating personalization challenges in mobile commerce: An empirical study. (January 2021) - Qusef, Abdallah; Albadarneh, Aalaa; Elish, Sameh; Muhanna, Muhanna
Highlights: The reception of personalization of Mobile Commerce and associated challenges was studied. The security concerns and potential risks impact the use of retail services, smartphone usage and privacy. Low bandwidth of mobile internet and network connectivity issues are associated with MC personalization. Abstract: This study investigates the reception of personalization of Mobile Commerce (MC) and its associated challenges. A specific focus has been given to the elements that influence client's satisfaction. The study adopts a quantitative study design in which data was collected through a survey conducted on 340 Mobile Commerce consumers. Data have been analysed through Pearson correlation, KMO and Bartlett's test, multiple regression analysis, and factor analysis. The findings of the analyses depict that security concerns and potential risks impact the use of retail services (correlation coefficient, 0.915; P< 0.05), and smartphone usage and privacy (correlation coefficient, 0.891; P< 0.05). Moreover, security hazards have been identified as the primary factor that influences the adjustment of Mobile Commerce administrations. The study findings are significant as they can be used to bring about improvements in the existing Mobile Commerce-based services that will lead to the increase in the customer satisfaction level and expansion of the loyal customer base. Graphical abstract: Image, graphical abstract